Challenges and opportunities to diabetes and endocrinology training during and beyond the COVID‐19 pandemic. (6th June 2022) - Vathenen, Ramu; Khan, Jansher; Edwards, Amy; Gelding, Susan V; Khanji, Mohammed Y; Gunganah, Kirun
Abstract: The COVID‐19 pandemic posed unprecedented new challenges to diabetes and endocrinology (D&E) training. We reflect from our local experience on its impact and lessons we can learn. Necessary restructuring of clinical services resulted in more general medicine and less inpatient specialty exposure. Outpatient clinic opportunities were reduced as clinics were postponed and virtual consultations became more frequent. Training opportunities such as local teaching and conferences were cancelled, and academic training often put on hold. Together these had a significant impact on training in D&E. However, the necessary restructuring can also be used to change D&E training for the better. Virtual consultations could improve opportunities for clinic attendance as physical space is a lesser issue. Remote access to clinical systems should be more widely available, thus promoting flexible working for trainees. The necessity for virtual teaching has seen the emergence of on‐demand services and the option of online attendance. Barriers to attending teaching, such as travel time and leave, are a lesser issue than ever before, particularly for conferences. The wellbeing of doctors is also being supported increasingly after the pandemic. The lessons we learn from this pandemic should be used to transform the face of D&E training and improve flexibility and job satisfaction. Such solutions can be applied to other current and future demands on specialty training. Copyright © 2022 John Wiley & Sons.